PENINGKATAN HASIL BELAJAR SISWA KELAS XI MELALUI MODEL PROJECT BASED LEARNING (PjBL) - jannah, shifaul (J-SES : Journal of Science, Education and Studies, 2024)
This research aims to improve student learning outcomes by using Project Based Learning (PjBL) method. This research was conducted on students in class XI-2 at SMAN 1 Sidoarjo using the Classroom Action Research (CAR) method. The research subjects were students in class XI-2 with a total of 32 students. The research was started through tests followed by 2 cycles of class action research. Before the class action research was held, the average value of student learning outcomes was 79. After the implementation of the first cycle of action, the average value of learning outcomes became 82.1. The higher average value of learning outcomes in the second cycle, it was 86.75. Based on these results, it can be concluded that the Project Based Learning method can improve student learning outcomes in class XI-2 at SMAN 1 Sidoarjo in history subjects.